Solid powder cosmetic
By using a cellulose powder with an average particle size of 1 μm to 25 μm and a length and width of 0.6 to 0.9 in the solid powder cosmetics, it solves the problem of difficulty in taking into account the problem of formation, impact resistance and smoothness in existing technologies, and achieves realization. A better sense of use and impact.
Patent Information
- Application Number
- CN202380047792.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-06-01
- Publication Date
- 2025-01-28
AI Technical Summary
When existing solid powder cosmetics improve moldability and impact resistance, they are difficult to take into account both smoothness and moisture, and are prone to fragmentation due to impact.
By containing cellulose powder with average particle size of 1 μm to 25 μm and a length of length of 0.6 to 0.9, the cohesion structure of the fine fiber cellulose is used to improve the molding and impact resistance of the powder, while maintaining smooth and humidity Touch.
The impact and smoothness and humidity of solid powder cosmetics are realized, which enhances the moldability and sense of use, and avoids the adverse situations that are broken due to impact.
Smart Images

Figure CN119384267A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to solid powder cosmetics. Background Art
[0002] In the past, solid powder cosmetics such as foundation and eye shadow were manufactured by a compression molding method in which a cosmetic composition is filled in a container and compressed to solidify. Since the amount of oil mixed in solid powder cosmetics is relatively small, the bonding force between the powders is weak and it is not easy to solidify. Therefore, although the compression pressure is increased for molding, the molded product manufactured in this way is hard and has a powdery touch.
[0003] Therefore, in order to obtain a moist, smooth and soft touch, elastic spherical resin powders such as silicone elastomers and polyurethanes are sometimes used in solid powder cosmetics. However, if a large amount of such resin powders are mixed, the solid powder cosmetics lack moldability and are easily broken by impact. It is difficult to produce such solid powder cosmetics that have both smoothness and impact resistance.
[0004] In Patent Document 1, by using an average compressive strength of 0.2 to 1 kg / mm 2 The organic powder is composed of 30 to 90 weight % of acylated taurine polyvalent metal salt and has an elastic modulus of 1 to 100 kg / cm 2 The above-mentioned difficulty is solved by using a film-forming polymer. Patent Document 2 focuses on an oil-soluble rice bran extract having excellent moisturizing properties and proposes a powder cosmetic in which an oil-soluble rice bran extract is mixed with an oil agent contained in a powder cosmetic at a specific ratio. Although the powder cosmetic is a powder, no friction is felt when applying it, and it is smooth. The powder is adsorbed on the skin, and the skin after application becomes smooth and soft to obtain a unique touch, and the damage caused by falling is reduced. In addition, Reference Document 3 proposes a color cosmetic containing cellulose particles.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2002-80325
[0008] Patent Document 2: Japanese Patent Application Publication No. 2021-98674
[0009] Patent Document 3: International Publication No. 2018 / 194050 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The techniques described in the above-mentioned Patent Documents 1 and 2 do not focus on the powder contained in the solid powder cosmetics, but focus on components other than the powder, such as a film-forming polymer or an oil-soluble rice bran extract, and impart impact resistance and a smooth touch to the solid powder cosmetics by mixing these components. In contrast, the inventors of the present invention focused on the powder and studied a powder that can be included in the solid powder cosmetics to obtain impact resistance and a smooth touch.
[0012] Means for solving problems
[0013] Furthermore, the inventors have conducted intensive studies and found that the above-mentioned problems can be solved by using a solid powder cosmetic containing cellulose powder, and the invention has been completed as follows: It should be noted that the cellulose particles described in Reference 3 are different from the cellulose powder of the present invention.
[0014] (First method)
[0015] A solid powder cosmetic, characterized in that it comprises cellulose powder having an average particle size of 1 μm to 25 μm and an aspect ratio of 0.6 to 0.9,
[0016] The cellulose powder is an aggregate containing an additive and fine fibrous cellulose having an average fiber width of 1 nm to 500 nm.
[0017] The cellulose powder contained in the above-mentioned solid powder cosmetics contains microfibrous cellulose. As the name suggests, microfibrous cellulose forms long and thin fibers, so the cellulose powder containing microfibrous cellulose is not spherical, but a shape deformed from a spherical shape. The deformed shape can be represented, for example, by the above-mentioned range of aspect ratios. If it is a solid powder cosmetic containing cellulose powder in the above-mentioned range of average particle size and range of aspect ratio, it can have both resistance to impact (impact resistance) and smoothness, moistness, soft touch and other feel during use. It is believed that the solid powder cosmetics containing the cellulose powder can take into account both impact resistance and feel during use due to the following reasons.
[0018] In order to improve the hardness and powdery feel that are the shortcomings of conventional solid powder cosmetics, studies have been conducted on the mixing of elastic spherical particles. However, elastic spherical particles are soft and have a smooth extension with a moist touch due to the rolling effect of the spheres. However, they are elastically deformed during compression molding, so when the pressure is released after molding, a force for recovery is exerted, making molding difficult, and the impact resistance after molding is also poor.
[0019] In contrast, it is speculated that the cellulose particles used in the present invention undergo plastic deformation when compressed, thereby increasing the contact area between the particles and improving the moldability and impact resistance of the solid powder cosmetic. In addition, it is assumed that even if there is no deformation due to pressure, the cellulose powder used in the present invention includes cellulose powder with deformed shape, and the specific surface area is larger than that of general spherical particles. In addition, since the powder is non-spherical, it is arranged in a random direction when mixed with the ingredients of the cosmetic, and the contact points between the ingredients are increased, thereby reducing the destruction by external forces that reduce the impact resistance.
[0020] In addition, if the dispersion of fine fibrous cellulose is dried directly, particles are formed in which the fibers are firmly and randomly bonded by hydrogen bonds. On the other hand, it is speculated that the cellulose powder containing fine fibrous cellulose and an additive (for example, a hydrophilic water-retaining agent) during drying can provide a moist touch because the additive appropriately inhibits the formation of hydrogen bonds between cellulose fibers, thereby adding softness, and can also obtain an effect of improving moldability due to plastic deformation.
[0021] In addition to the first aspect, the following aspects are also preferred aspects.
[0022] (Second method)
[0023] In the solid powder cosmetic of the first aspect, the cellulose powder is formed by agglomeration of the fine fibrous cellulose.
[0024] (Third method)
[0025] The solid powder cosmetic according to the first aspect contains 60% to 99.9% by mass of the powder comprising the cellulose powder and 0.1% to 40% by mass of oil.
[0026] (Fourth method)
[0027] In the solid powder cosmetic according to the first aspect, the additive is glycerin.
[0028] (Fifth method)
[0029] In the solid powder cosmetic of the first aspect, the cellulose powder has a water content of 1% to 15% in an atmosphere with a humidity of 50%.
[0030] (Sixth method)
[0031] The solid powder cosmetic of the first embodiment, wherein the bulk specific gravity of the cellulose powder is 0.5 g / cm 3 the following.
[0032] (Seventh method)
[0033] The solid powder cosmetic of the first embodiment, wherein the specific surface area of the cellulose powder is 1.0 m 2 / g or above.
[0034] (Eighth Method)
[0035] The solid powder cosmetic according to the first aspect comprises 1% by mass to 99% by mass of the cellulose powder.
[0036] (9th method)
[0037] In the solid powder cosmetic of the first aspect, the cellulose powder has a cellulose pulp viscosity of 1.0 mPa·s to 7.0 mPa·s.
[0038] (10th method)
[0039] The solid powder cosmetic according to the first aspect is a base makeup cosmetic.
[0040] Effects of the Invention
[0041] According to the present invention, a smooth solid powder cosmetic having resistance to impact (impact resistance) is obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 is a SEM image of cellulose powder A.
[0043] Figure 2 is a SEM image of cellulose powder B.
[0044] Figure 3 is a SEM image of cellulose powder C.
[0045] Figure 4 is a SEM image of cellulose powder D.
[0046] Figure 5 This is a SEM image of silicone powder.
[0047] Figure 6 This is a SEM image of silica powder. DETAILED DESCRIPTION
[0048] Next, a specific embodiment will be described. It should be noted that this embodiment is an example of the present invention, and the scope of the present invention is not limited to the scope of this embodiment.
[0049] The solid powder cosmetic of this embodiment is characterized in that it contains cellulose powder having an average particle size of 1 μm to 25 μm and an aspect ratio of 0.6 to 0.9, and the cellulose powder is an aggregate of fine fibrous cellulose containing an additive and an average fiber width of 1 nm to 500 nm. The composition of the solid powder cosmetic is described below.
[0050] (Microfibrous cellulose)
[0051] The cellulose powder contained in the solid powder cosmetic of the present embodiment contains fine fibrous cellulose (also referred to as "CNF") which can be obtained by fibrillating (refining) raw material pulp.
[0052] As the raw material pulp of the fine fibrous cellulose, one or more kinds can be selected from wood pulp made from broad-leaved trees, coniferous trees, etc., non-wood pulp made from straw, bagasse, cotton, hemp, bast fiber, etc., and waste paper pulp (DIP) made from recycled waste paper, broken paper, etc.
[0053] However, from the perspective of avoiding the mixing of impurities as much as possible and obtaining alkali-insoluble α-cellulose by mixing a high amount of cellulose components, it is preferable to use wood pulp rather than non-wood pulp or waste paper pulp. By treating with alkali, alkali-soluble components can be removed and the purity of cellulose can be improved.
[0054] As the wood pulp, one or more kinds can be selected from chemical pulps such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP), mechanical pulp (TMP), and the like, for example.
[0055] The hardwood kraft pulp may be hardwood bleached kraft pulp, hardwood unbleached kraft pulp, or hardwood semi-bleached kraft pulp. Similarly, the conifer kraft pulp may be conifer bleached kraft pulp, conifer unbleached kraft pulp, or conifer semi-bleached kraft pulp.
[0056] As the mechanical pulp, one or more kinds of pulp can be selected from stone ground pulp (SGP), pressure stone ground pulp (PGW), wood ground pulp (RGP), chemical ground pulp (CGP), thermo ground pulp (TGP), grinding pulp (GP), thermomechanical pulp (TMP), chemical thermomechanical pulp (CTMP), refiner mechanical pulp (RMP), bleached thermomechanical pulp (BTMP), etc. However, in order to avoid the mixing of impurities other than cellulose, it is particularly preferable to use chemical pulp such as broadleaf kraft pulp (LKP) and coniferous kraft pulp (NKP).
[0057] Before the microfibrous cellulose is fibrillated, it is also possible to perform a pretreatment by a chemical method. Examples of the pretreatment by a chemical method include hydrolysis of polysaccharides by acid (acid treatment), hydrolysis of polysaccharides by enzymes (enzyme treatment), swelling of polysaccharides by alkali (alkali treatment), oxidation of polysaccharides by oxidants (oxidation treatment), and reduction of polysaccharides by reducing agents (reduction treatment).
[0058] When alkali treatment is performed before fibrillation, the hydroxyl groups of hemicellulose or cellulose contained in the pulp are partially dissociated and the molecules are anionized, thereby weakening the intramolecular and intermolecular hydrogen bonds and promoting the dispersion of the cellulose fibers during fibrillation.
[0059] As the alkali used in the alkali treatment, for example, organic bases such as sodium hydroxide, lithium hydroxide, potassium hydroxide, aqueous ammonia solution, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and benzyltrimethylammonium hydroxide can be used. Among them, sodium hydroxide is preferably used from the viewpoint of production cost.
[0060] If enzyme treatment, acid treatment, or oxidation treatment is performed before fiber opening, the water retention of the microfibrous cellulose can be reduced, the crystallinity can be increased, and the homogeneity can be improved. In this regard, when the water retention of the microfibrous cellulose is low, it is easy to dehydrate, and the dehydration property of the dispersion of the microfibrous cellulose (hereinafter also referred to as "slurry") is improved.
[0061] If the raw material pulp is subjected to enzyme treatment, acid treatment, and oxidation treatment, the amorphous region of hemicellulose or cellulose possessed by the pulp is decomposed. If the amorphous region is decomposed in advance, the energy required for the pulp to be micronized can be reduced, and the homogeneity and dispersibility of the cellulose fibers can be improved. If the homogeneity and dispersibility of the cellulose fibers are excellent, the cellulose powder manufactured from the microfibrous cellulose has a tendency to have a small deviation in particle size and be homogeneous. If the deviation in the particle size of the cellulose powder is large, the cellulose powder cannot be fully dispersed in the solid powder cosmetics and may exist unevenly. Therefore, the degree of decomposition of the amorphous region of hemicellulose and cellulose possessed by the pulp is one of the important factors. However, pretreatment can also reduce the aspect ratio of the microfibrous cellulose, and manufacture a cellulose powder that deviates from the desired average particle size, so it is preferred to avoid excessive pretreatment.
[0062] The fiber opening of the raw material pulp can be performed by beating the raw material pulp using a homogenizer such as a refiner, a high pressure homogenizer, a high pressure homogenizer, a grinding mill, a grinding mill such as a grinder, a pulverizer, a single shaft kneading mill, a multi-shaft kneading mill, a kneading refiner, a jet mill, etc. However, it is preferably performed using a refiner or a jet mill.
[0063] The fiberizing of the raw material pulp is preferably carried out in such a manner that the average fiber diameter, average fiber length, water retention, crystallinity, coefficient of variation of fiber diameter distribution, peak value in the simulated particle size distribution curve, pulp viscosity, and B-type viscosity of the dispersion (slurry) of the obtained fine fibrous cellulose become the desired values or evaluations shown below.
[0064] The average fiber diameter (average fiber width; average diameter of single fibers) of the microfibrous cellulose is preferably 1 nm to 500 nm, more preferably 3 nm to 500 nm, and particularly preferably 10 nm to 100 nm. If the average fiber diameter of the microfibrous cellulose is less than 1 nm, the viscosity becomes high when the microfibrous cellulose is made into a slurry, making it difficult to dry the microfibrous cellulose to produce a cellulose powder. In addition, depending on the production method, the cellulose may dissolve and the fiber shape may not be maintained.
[0065] On the other hand, if the average fiber diameter of the fine fibrous cellulose exceeds 500 nm, the average particle size of the cellulose powder becomes larger, and the shape becomes more deformed such as closer to a rod or a flat shape, and the solid powder cosmetic containing the cellulose powder may easily become rough or feel like a foreign body.
[0066] The average fiber diameter of the fine fibrous cellulose can be adjusted by, for example, selecting raw material pulp, pre-treating it, fibrillating it, and the like.
[0067] The method for measuring the average fiber diameter of the fine fibrous cellulose is as follows.
[0068] First, 100 ml of an aqueous dispersion (slurry) of fine fibrous cellulose having a solid content concentration of 0.01% to 0.1% by mass is filtered with a Teflon (registered trademark) membrane filter, and solvent replacement is performed once with 100 ml of ethanol and three times with 20 ml of tert-butyl alcohol. Next, freeze-drying is performed and osmium coating is performed to prepare a sample. For this sample, observation based on an electron microscope SEM image is performed at any magnification of 3000 times to 30000 times according to the width of the constituent fibers. Specifically, two diagonal lines are drawn on the observed image, and three straight lines passing through the intersection of the diagonal lines are drawn arbitrarily. Furthermore, the width of a total of 100 fibers intersecting these three straight lines is visually measured. In addition, the median diameter of the measured value is taken as the average fiber diameter.
[0069] The average fiber length of the fine fibrous cellulose (average length of single fibers) is preferably 0.3 μm to 200 μm, more preferably 0.4 μm to 200 μm, and particularly preferably 0.5 μm to 200 μm. If the average fiber length of the fine fibrous cellulose is less than 0.3 μm, the fibers are poorly aggregated, making it difficult to produce a cellulose powder having a desired average particle size, and there is a possibility that a cellulose powder with a small particle size or aggregated bundle-like particles may be produced in large quantities.
[0070] On the other hand, when the average fiber length of the fine fibrous cellulose exceeds 200 μm, the cellulose tends to become powders of various shapes, which causes non-uniformity in particle shape and non-uniformity in particle size.
[0071] The average fiber length of the microfibrous cellulose can be adjusted by, for example, selecting raw material pulp, pre-treating it, fibrillating it, and the like.
[0072] The average fiber length of the microfibrous cellulose is measured in the same manner as the average fiber diameter, by visually measuring the length of each fiber, and the median length of the measured values is taken as the average fiber length.
[0073] The aspect ratio of the fine fibrous cellulose is preferably 50 to 200,000, more preferably 50 to 10,000. If the aspect ratio is less than 50, it is difficult to obtain a cellulose powder having a desired average particle size. On the other hand, if the aspect ratio exceeds 200,000, the circularity of the cellulose powder becomes small, which may impair the smoothness of the solid powder cosmetic.
[0074] The lower limit of the crystallinity of the fine fibrous cellulose may be 50 or more, more preferably 60 or more, particularly preferably 70 or more, and the upper limit may be 100 or less, more preferably 95 or less, particularly preferably 90 or less. If the crystallinity is less than 50, the strength of the cellulose powder is low, and a solid powder cosmetic having excellent impact resistance may not be obtained.
[0075] If no chemical modification treatment is performed, the water retention of the microfibrous cellulose is preferably 500% or less, more preferably 300% to 480%. If the water retention of the microfibrous cellulose is less than 300%, the microfibrous cellulose cannot be opened to a desired size, and as a result, particles of a desired shape and size may not be obtained.
[0076] On the other hand, if the water retention rate of the microfibrous cellulose exceeds 500%, the water retention capacity of the microfibrous cellulose itself increases, and the drying process of the microfibrous cellulose takes a lot of time.
[0077] The water retention of fine fibrous cellulose can be adjusted by, for example, selecting raw material pulp, pre-treating it, fibrillating it, and the like.
[0078] The water retention capacity of fine fibrous cellulose is a value measured in accordance with JAPAN TAPPI No. 26 (2000).
[0079] The pulp viscosity of the fine fibrous cellulose is preferably 1.0 mPa·s to 7.0 mPa·s, more preferably 1.5 mPa·s to 6.5 mPa·s, and particularly preferably 2.0 mPa·s to 6.0 mPa·s. In addition, the degree of polymerization of the fine fibrous cellulose used in the cellulose powder is preferably 150 to 1250, more preferably 250 to 1150. The pulp viscosity is the viscosity of the solution after dissolving cellulose in a copper ethylenediamine solution. The greater the pulp viscosity, the greater the degree of polymerization of the cellulose. In addition, the pulp viscosity is related to the strength and rigidity of the cellulose fiber. If the polymerization degree is too high, the cellulose powder becomes hard, and even if the additives are mixed, it will become a rough solid powder cosmetic. On the other hand, if the polymerization degree is too low, the strength of the fiber itself is also lost, and the plastic force required for the cellulose powder used in the present invention becomes excessive, making it difficult to control the formability of the cosmetic itself. The degree of polymerization of the fine fibrous cellulose can be adjusted, for example, by selecting the raw pulp, pre-treating, and fiberizing. If the pulp viscosity is within the above range, the particles have good plasticity and become a solid powder cosmetic with impact resistance and smoothness.
[0080] The fine fibrous cellulose obtained by fiber opening can be pre-dispersed in an aqueous medium as needed to prepare a dispersion (slurry). The aqueous medium is particularly preferably water (aqueous solution) in its entirety. However, the aqueous medium may also be other liquids that are partially miscible with water. As other liquids, for example, lower alcohols having a carbon number of 3 or less can be used.
[0081] The dispersion of fine fibrous cellulose (slurry, 2.0% by mass based on solid content) can be adjusted in advance to preferably a B-type viscosity of 400 mPa·s to 100,000 mPa·s, more preferably 500 mPa·s to 50,000 mPa·s. If the B-type viscosity of the dispersion is adjusted in advance to be within the above range, the slurry can be supplied to the drying device in the drying step without clogging.
[0082] The B-type viscosity of the dispersion of fine fibrous cellulose is a value measured in accordance with "Methods for measuring viscosity of liquids" of JIS-Z8803 (2011). The B-type viscosity is the resistance torque when the dispersion is stirred, and a higher value means more energy is required for stirring.
[0083] The fibrillation of cellulose fibers can be performed by the fibrillation device and method shown below. The fibrillation can be performed by selecting one or more means from homogenizers such as high-pressure homogenizers and high-pressure homogenization devices, stone mill friction machines such as grinders and grinders, refiners such as conical refiners and disc refiners, various bacteria, etc. However, the fibrillation of cellulose fibers is preferably performed using a device and method that utilizes water flow, especially high-pressure water flow, for micronization. According to the device and method, the uniformity of size and dispersion of the obtained microfibrous cellulose is very high. In contrast, for example, if a grinder that grinds between rotating grindstones is used, it is difficult to uniformly micronize the cellulose fibers, and depending on the situation, there may be undissolved fiber clumps remaining locally.
[0084] Examples of grinding machines used in the fiber opening of cellulose fibers include Masscolloder manufactured by Masuko Sangyo Co., Ltd. In addition, examples of devices that utilize high-pressure water flow for micronization include Star Burst (registered trademark) manufactured by Sugino Machine Co., Ltd. and Nanovater (registered trademark) manufactured by Yoshida Machine Co., Ltd. In addition, examples of high-speed rotary homogenizers used in the fiber opening of cellulose fibers include CLEARMIX-11S manufactured by M-technique Co., Ltd.
[0085] The solid powder cosmetic of this embodiment contains cellulose powder, but may contain powder Y other than cellulose powder. In this specification, the concept of containing cellulose powder and powder Y other than cellulose powder is sometimes referred to as "powder", "powder containing cellulose powder", etc.
[0086] (Cellulose powder)
[0087] The cellulose powder of the present embodiment is an aggregate formed by drying microfibrous cellulose. Microscopically, there are cellulose powders formed by drying microfibrous cellulose in a monomeric state (e.g., a cellulose powder formed by a filament entangled in a filament, a cellulose powder formed by drying thoroughly), and there are also cases where multiple microfibrous celluloses are aggregated during drying to form an aggregate. Microfibrous cellulose is made from raw pulp. If dried, the fibers will wrinkle and shrink, so the cellulose powder formed is difficult to express but has a concave-convex shape, such as a shape formed by the aggregation of thoroughly dried microfibrous cellulose, a shape of candy, and a shape formed by crumpling and kneading one or more sheets of Japanese white paper and the like. In addition, the cellulose powder is white, light yellow, cream, light orange, or a mixture of these colors. In particular, if it is a white or light yellow cellulose powder, it is not conspicuous as a composition of solid powder cosmetics, so it is preferred.
[0088] The cellulose powder of the present embodiment preferably contains 50% by mass or more, more preferably 60% by mass or more, and still more preferably 70% by mass or more of fine fibrous cellulose, and the upper limit may be 100% by mass. When the mass percentage of fine fibrous cellulose in the cellulose powder is less than 50% by mass, the cellulose powder may not have the desired average particle size and aspect ratio.
[0089] In addition, the cellulose powder has uneven surfaces due to the fine wrinkles formed on the surface, so that light irradiated from the outside is irradiated to the uneven surfaces and diffusely reflected at various angles. Therefore, the surface of the cellulose powder lacks glossiness, and the solid powder cosmetic containing the cellulose powder suppresses oiliness.
[0090] In addition, the cellulose powder of the present embodiment is produced by drying, for example, so there is a case where a plurality of dried and wrinkled fine fibrous celluloses are entangled to form unevenness on the surface. There are various ways to dry the fine fibrous cellulose, and the formed cellulose powder becomes a particle in the shape of a single dried fine fibrous cellulose or a particle in the shape of a plurality of aggregated particles.
[0091] The average particle size of the cellulose powder contained in the solid powder cosmetic of the present embodiment is preferably 1 μm to 25 μm, more preferably 2 μm to 24 μm, and further preferably 3 μm to 23 μm, and the aspect ratio is preferably 0.6 to 0.90, and more preferably 0.6 to 0.85. If the average particle size and aspect ratio of the cellulose powder are in the above range, the solid powder cosmetic has impact resistance and smoothness. In order to take into account both impact resistance and smoothness, it is preferred that the values of the average particle size and the aspect ratio are within the above range, and it is not preferred that either deviate from the above range. For example, even if the average particle size of the cellulose powder is within the above range, if the aspect ratio exceeds the above range, the impact resistance of the solid powder cosmetic may be impaired. In addition, even if the aspect ratio of the cellulose powder is within the above range, if the average particle size exceeds the above range, the smoothness of the solid powder cosmetic may be impaired. It should be noted that the aspect ratio of the cellulose powder refers to the value obtained by dividing the minor axis diameter of the cellulose powder by the major axis diameter of the cellulose powder.
[0092] The moisture content of cellulose powder in an atmosphere with a humidity of 50% is preferably 1% to 15%, more preferably 3% to 10%. If the moisture content of cellulose powder is within the above range, the impact resistance of solid powder cosmetics will be more excellent. The moisture content of cellulose powder can be adjusted by the concentration of microfibrous cellulose in the microfibrous cellulose dispersion liquid as the raw material of cellulose powder, the drying time, the average fiber width of microfibrous cellulose, etc. However, depending on the drying method described later, it is sometimes difficult to adjust the moisture content of cellulose powder to less than the lower limit of the above range. In addition, if the moisture content of cellulose powder exceeds the above range, the solid powder cosmetics may deteriorate due to long-term use.
[0093] The bulk density of cellulose powder is 0.5g / cm 3 Below, preferably 0.1 g / cm 3 ~0.5g / cm 3 , more preferably 0.1 g / cm 3 ~0.4g / cm 3 If the bulk density of cellulose powder exceeds 0.5g / cm 3 , the solid powder cosmetics lack the adhesion feeling (adhesion feeling refers to the feeling that the solid powder cosmetics are fully adhered to the application object such as the skin), and it is difficult to feel the moist feeling, making it difficult to use a puff to take the solid powder cosmetics.
[0094] The circularity of the cellulose powder is preferably 0.5 to 0.9, more preferably 0.6 to 0.85. When the circularity of the cellulose powder is within the above range, a solid powder cosmetic having excellent impact resistance and smoothness is obtained. When the circularity is less than 0.5, the smoothness is reduced, and when it exceeds 0.9, the impact resistance may be reduced.
[0095] The aspect ratio and circularity can be measured using a Morphologi 4 manufactured by Malvern Panalytical. These values are obtained by: 3 The particles were collected in a sample box, dispersed on a glass plate using a dispersion unit, and analyzed by a static image analysis method with a particle count of 20,000.
[0096] Compressive strength of cellulose powder: 10% strength is preferably 5 MPa or less, more preferably 0.5 MPa to 5 MPa. If the compressive strength of cellulose powder exceeds 5 MPa, hardness and roughness may be felt, and smoothness may be lacking.
[0097] The specific surface area of cellulose powder is preferably 1.0 m 2 / g or more, more preferably 1.0 m 2 / g~10m 2 / g, more preferably 1.5m2 / g~8m 2 / g. If the specific surface area is less than 1.0m 2 / g, the surface of the cellulose powder has few irregularities, so the adhesion of the solid powder cosmetic is poor, and a dry and powdery feel becomes noticeable.
[0098] (additive)
[0099] In order to bring about the effect of improving the dispersibility of the cellulose powder manufactured by the above-mentioned drying process in the composition of the solid powder cosmetics, the effect of preventing the skin from drying, and the effect of imparting moisturizing (skin moisturizing effect), additives can be contained in the cellulose powder. This is because the cellulose powder sometimes agglomerates with each other when it is placed after manufacturing. One of the reasons is believed to be the polarity of the cellulose molecules constituting the cellulose powder. Therefore, in the solid powder cosmetics, the cellulose powder is sometimes not dispersed as a whole, but exists unevenly. Therefore, by pre-containing additives in the cellulose powder, the polarity of the cellulose molecules in the cellulose powder is masked, and the cellulose powder is difficult to agglomerate with each other, and it is easy to disperse in the solid powder cosmetics as a whole. The additives in the invention of this application can be any substance that can mask the polarity of the cellulose molecules, or a substance that physically prevents the cellulose fibers from firmly agglomerating with each other during drying. From the perspective of mixing with the dispersion of cellulose fibers in advance, it is preferably a hydrophilic material, and more preferably a hydrophilic material having an OH group (hydroxyl group), a CO group (carbonyl group), and a COOH group (carboxyl group). The cellulose powder of the present embodiment is hydrophilic, and therefore, by containing the additive as a hydrophilic material, the water content of the cellulose powder is maintained within a desired range, and the solid powder cosmetic has excellent impact resistance.
[0100] As additives, one or more selected from polyols, polysaccharides, water-soluble polymers, and surfactants can be used. The content of the additives in the cellulose powder can be preferably 1% to 49% by mass, more preferably 2% to 48% by mass. If the content is too high, the cellulose powder becomes sticky or loses its lightness, and the adhesion to the skin is deteriorated. On the other hand, if the content is too low, the above-mentioned dispersion effect and emollient effect may not be achieved.
[0101] As the additive, polyols include polyols having 2 to 6 carbon atoms and 2 to 3 oxygen atoms. Specifically, glycerol, diglycerol, propylene glycol, 1,3-butylene glycol, 1,2-pentanediol, dipropylene glycol, 1,2-hexanediol, heptanediol, ethylene glycol, diethylene glycol, 1,3-propylene glycol, 3-methyl-1,3-butylene glycol, etc. can be used, but are not limited to these. Glycerol is particularly preferred from the perspective of thickening properties and dispersibility of composite particles.
[0102] As the polysaccharide, quince seeds, magnesium aluminum silicate (Veegum), xanthan gum, hyaluronate and the like can be used, but are not limited thereto. Hyaluronate and the like are particularly preferred from the viewpoint of thickening properties and dispersibility of cellulose powder.
[0103] As water-soluble polymers, polyvinyl alcohol, polyvinyl pyrrolidone, carboxyvinyl polymer, polyethylene glycol, homopolymers or copolymers of monomers having phosphorylcholine groups as constituent monomers, homopolymers or copolymers of monomers having sugar residues as constituent monomers, and homopolymers or copolymers of monomers having amino acid residues as constituent monomers can be cited. Specifically, copolymers consisting of (meth) alkyl acrylates and polymethacryloyloxyethyl phosphorylcholine, copolymers consisting of (meth) alkyl acrylates and methacryloyloxyethyl glucoside, copolymers consisting of (meth) alkyl acrylates and methacryloyl-L-lysine, etc. can be exemplified, but are not limited to these. From the aspects of thickening and dispersibility of cellulose powder, polyvinyl pyrrolidone is particularly preferred.
[0104] As surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants can be cited. In particular, nonionic surfactants are preferred to eliminate the influence of ionic bonds. On the other hand, if a cationic surfactant is added to anionic cellulose fibers, the cellulose fibers will be excessively agglomerated during powder production (drying), and the shape control of the powder may become difficult.
[0105] Examples of nonionic surfactants include polyoxyalkylene alkyl ethers, glycerol alkyl ethers, glycerol fatty acid esters, polyglycerol fatty acid esters, sorbitan fatty acid esters and alkylene glycol adducts thereof, polyalkylene glycol fatty acid esters, polyglycerol modified silicones, polyether modified silicones, and the like. Examples of anionic surfactants include alkyl phosphates, polyoxyalkylene alkyl ether phosphates, sulfonates, alkyl sulfates, polyaspartates, and the like. Examples of cationic surfactants include alkylamine salts, alkyltrimethylammonium salts, and the like. Examples of amphoteric surfactants include hydrogenated lecithin, carboxybetaine type amphoteric surfactants, sulfobetaine type amphoteric surfactants, and amino acid type amphoteric surfactants, and the like.
[0106] (Inorganic particles)
[0107] Cellulose powder may contain inorganic particles. Inorganic particles can impart various functions to cellulose powder. For example, metallic inorganic particles have the function of diffusely reflecting incident light. By including such inorganic particles in cellulose powder, it is expected that the effects of suppressing ultraviolet radiation and suppressing the oiliness of the skin at the applied part can be achieved.
[0108] The upper limit of the content of inorganic particles in cellulose powder can be 49% by mass, preferably 45% by mass or less, and the lower limit can be 0% by mass, preferably 5% by mass or more. If the content exceeds 49% by mass, the specific gravity of cellulose powder becomes large corresponding to the inclusion of inorganic particles, and the dispersibility in solid powder cosmetics may be impaired. On the other hand, if the content is 5% by mass or more, the effect of diffuse reflection of incident light can be fully exerted.
[0109] The upper limit of the primary particle size of the inorganic microparticles can be 10 μm, preferably 5 μm or less, and more preferably 1 μm or less. If the primary particle size of the inorganic microparticles exceeds 10 μm, it is difficult for the inorganic microparticles to be supported by the fine fibrous cellulose. The lower limit of the primary particle size of the inorganic microparticles is not particularly limited, and can be 1 nm, preferably 2 nm or more, and more preferably 3 nm or more. If the primary particle size of the inorganic microparticles is 1 nm or more, when the inorganic microparticles are mixed with the raw material slurry for manufacturing the cellulose powder, the inorganic microparticles are easily dispersed and entangled in the fine fibrous cellulose.
[0110] The primary particle size of the inorganic fine particles can be measured by electron microscope observation, and the average value of the obtained particle sizes is taken as a measured value.
[0111] Inorganic particles can of course be used directly, but if they are hydrophilic treated, they are easy to adapt to the raw material slurry for manufacturing cellulose powder, so they are preferred. The surface treatment agent used in the hydrophilic treatment has the effect of suppressing the surface activity of inorganic particles, improving the dispersibility of inorganic particles, and improving transparency and roughness. As the surface treatment agent of inorganic particles, there is no particular limitation as long as it can be dispersed in the raw material slurry, and preferably includes silicic anhydride and hydrous silicic acid.
[0112] Inorganic particles are not particularly limited, and known inorganic particles can be used, such as barium titanate, lead zirconate titanate, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, zirconium oxide, zircon, titanium oxide, zinc oxide, iron oxide, cerium oxide, etc. can be cited. When improving the effect of suppressing ultraviolet radiation, suppressing the effect of skin gloss, for example, one or more combinations selected from the group consisting of titanium oxide, zinc oxide, iron oxide, and cerium oxide can be used. Especially when the inorganic particles are titanium oxide, the effect of suppressing ultraviolet radiation is improved, so it is preferred.
[0113] The shape of the inorganic fine particles that can be contained in the cellulose powder is not particularly limited, and may be, for example, spherical, rod-shaped, needle-shaped, spindle-shaped, plate-shaped, polygonal, or the like.
[0114] The inorganic particles may be attached to the surface of the fine fibrous cellulose in the cellulose powder, or may be encapsulated in the fine fibrous cellulose. If the inorganic particles are encapsulated in the fine fibrous cellulose, the cellulose powder can carry the inorganic particles not only on the surface but also inside, and diffuse reflection occurs even when incident light is irradiated from various angles, so it is preferred. Here, encapsulation may refer to a state in which a part of the surface of the inorganic particles is covered with the fine fibrous cellulose, or a state in which the inorganic particles are covered with the fine fibrous cellulose and cannot be observed from the outside when the cellulose powder is observed from the outside.
[0115] The inorganic fine particles may be added to the fine fibrous cellulose dispersion before drying and mixed uniformly.
[0116] The solid powder cosmetic of this embodiment may contain cellulose powder in an amount of preferably 1 to 99 mass%, more preferably 3 to 60 mass%, and even more preferably 5 to 40 mass%. If the cellulose powder is less than 1 mass%, the solid powder cosmetic lacks impact resistance.
[0117] (Manufacturing of cellulose powder)
[0118] The cellulose powder can be produced by drying fine fibrous cellulose in a drying process. Specifically, as a fine fibrous cellulose raw material, it can be produced by freeze drying, reduced pressure drying, heating drying (for example, drying by heat drying), spray drying, and spray freezing / reduced pressure drying as a drying method of the cellulose powder of this embodiment. In particular, the average particle size and aspect ratio of the cellulose powder produced by the heating drying method and the spray drying method are suitable as the composition of the solid powder cosmetic of this embodiment.
[0119] Among the heat drying methods, the method for producing cellulose powder by drum drying can obtain a dried product that is easily dispersed without agglomerating even fine fibrous cellulose of relatively high concentration or lack of fluidity. As an example, the production of cellulose powder by drum drying is performed as follows.
[0120] For example, the microfibrous cellulose can be supplied to a drum dryer for drying in a slurry (water dispersion) state, and the content of the microfibrous cellulose (absolute dry mass%) is 1% by mass or more, preferably 1.5% by mass, and more preferably 2.0% by mass. In addition, the content is 10% by mass or less, preferably 7% by mass, and more preferably 5% by mass. If the content exceeds 10% by mass, the viscosity of the slurry is too high and lacks operability. On the other hand, if the content is less than 1% by mass, a large amount of energy and time are consumed to remove water, which is uneconomical.
[0121] The drum dryer used in the drying process based on the drum drying method can be a well-known drum dryer. For example, the "John Millder JM-T model" produced by Johnson Boiler Company can be used. As the drum dryer, an internal rotary drum dryer can be preferably used. If it is an internal rotary drum dryer, the drying process is carried out smoothly, and a dried body with a relatively small specific surface area is obtained. The drying process can be carried out under normal pressure.
[0122] Regarding the operating conditions of the drum dryer, the surface temperature of the inner surface of the drum is 80°C to 200°C, preferably 90°C to 190°C. If it is this surface temperature, a dry body with strong cohesive force can be obtained. If the surface temperature exceeds 200°C, part of the fibers of the fine fibrous cellulose may cause thermal denaturation. On the other hand, if the surface temperature is less than 80°C, not only will it take a lot of time to remove the water, but the particles will also have very high moisture content. In addition, the rotation speed of the drum dryer also depends on the inner diameter of the drum and the amount of slurry input, for example, it can be set to more than 0.5rpm and less than 2rpm. The time for drying using a drum dryer also depends on the amount of slurry input, but if it is 1 second to 60 seconds, it is fully dried, and even if the drying exceeds this time, the moisture content of the dry body will not be further reduced.
[0123] As an apparatus used when producing cellulose powder by a spray drying method, a spray drying apparatus ("P-260" manufactured by PRECI) can be exemplified. Cellulose powder can be produced by supplying a slurry of fine fibrous cellulose to the spray drying apparatus. The spray drying apparatus is, for example, a two-fluid nozzle method, and an apparatus equipped with two 90-type nozzles can be used. Regarding the conditions for spray drying, for example, the slurry of fine fibrous cellulose can be 20 kg / h, the inlet temperature of the drying air can be 200°C, the outlet temperature can be 100°C, and the spray air pressure can be 0.6 MPa, but it is not limited to these.
[0124] When producing a cellulose powder containing the above-mentioned additive, the additive can be mixed with a slurry of fine fibrous cellulose as a manufacturing raw material to prepare a mixture, and the mixture can be supplied to a drying device (such as a drum dryer or a spray dryer) used in a heat drying method or a spray drying method.
[0125] (oil content)
[0126] The solid powder cosmetic of this embodiment may contain oil. By including oil in the solid powder cosmetic, the moldability is improved and the impact resistance is excellent. However, since the solid powder cosmetic contains cellulose powder, even with a smaller amount of oil than conventional cosmetics, good impact resistance can be obtained.
[0127] As the oil component, any oil can be used regardless of its origin, such as animal oil, vegetable oil, synthetic oil, etc., and its properties, such as solid oil, semi-solid oil, liquid oil, volatile oil, etc.
[0128] As the oil component, one or a combination of two or more selected from hydrocarbons, fats, waxes, hardened oils, ester oils, fatty acids, silicone oils, fluorinated oils, lanolin derivatives, oil-soluble ultraviolet absorbers, etc. can be used.
[0129] More specifically, hydrocarbons such as liquid paraffin, squalane, vaseline, paraffin, ceresin, microcrystalline wax, wood wax, and montan wax can be used; oils and fats such as olive oil, castor oil, jojoba oil, mink oil, and macadamia oil; waxes such as beeswax, lanolin, carnauba wax, candelilla wax, and spermaceti; esters such as isostearyl isostearate, cetyl isooctanoate, isopropyl myristate, isopropyl palmitate, octyldodecyl myristate, tricaprylin, glyceryl tribehenate, pentaerythritol rosinate, diisostearyl malate, dilinoleic acid dimer dilinoleate, and neopentyl glycol dioctanoate; low-polymerization degree dimethyl polysiloxane, high-polymerization degree dimethyl polysiloxane, methylphenyl polysiloxane, (dimethylsiloxane / ethylene) polysiloxane, Silicones such as silicone gel composed of cross-linked silicone such as polydimethylsiloxane (PDMS) cross-linked polymer and solvent, fluorine-modified silicone; fluorine-based oils such as perfluoropolyether, perfluorodecane, and perfluorooctane; lanolin derivatives such as lanolin, lanolin acetate, lanolin fatty acid isopropyl, and lanolin alcohol; lipophilic surfactants with an HLB value of 8 or less such as sorbitan isostearate, sorbitan sesquiisostearate, polyglyceryl-2 isostearate, and polyglyceryl-2 diisostearate; oil-soluble ultraviolet absorbers such as ethylhexyl methoxycinnamate, ethylhexyl dimethyl PABA, diethylaminohydroxybenzoyl hexyl benzoate, ethylhexyl triazone, and bis-ethylhexyloxyphenol methoxyphenyl triazine, etc., or a combination of one or more of them. Among these, when one or a combination of two or more selected from high-viscosity ester oils having a viscosity of 1,000 to 50,000 mPa·s at 25° C. such as diisostearyl malate and dimer dilinoleate, and lipophilic surfactants such as sorbitan sesquiisostearate and polyglyceryl-2 diisostearate are used, moldability and moist touch feel are further improved.
[0130] The content of oil in the solid powder cosmetic of the present embodiment is preferably 0.1% to 40% by mass, more preferably 0.1% to 25% by mass, and particularly preferably 1% to 15% by mass. If the content of oil is less than 0.1% by mass, the moldability may be reduced. On the other hand, if the content of the oil exceeds 40% by mass, the application on a makeup puff such as a sponge becomes poor, and it is difficult to spread the cosmetics on the skin. The solid powder cosmetic of the present embodiment contains cellulose powder, so it is possible to maintain moldability with less oil than the usual amount of oil, so it can be made into a cosmetic that is easy to apply and easy to spread.
[0131] (Other powders Y)
[0132] The solid powder cosmetic of this embodiment may be mixed with a powder Y other than the cellulose powder. If the powder Y is included, the stickiness of the makeup film can be further suppressed, and when the solid powder cosmetic of this embodiment is used as a base makeup cosmetic, the covering power and makeup feeling can be made to be the desired values. The average particle size of the powder Y other than the cellulose powder is 0.01 μm to 200 μm.
[0133] The powder Y other than cellulose powder is not limited by shapes such as spheres, plates, spindles, needles, particle sizes, porous, non-porous particle structures, etc. In addition, the powder Y other than cellulose powder can be one or a combination of two or more selected from inorganic coloring pigments, inorganic extender pigments, inorganic fine particle powders, bright powders, organic extender pigments, and organic coloring pigments.
[0134] As the powder Y other than the cellulose powder, specifically, for example, inorganic coloring pigments selected from titanium oxide, zinc oxide, zirconium oxide, red iron oxide, yellow iron oxide, black iron oxide, carbon black, chromium hydroxide, Prussian blue, ultramarine, etc.; mica, sericite, talc, kaolin, synthetic phlogopite, silicic anhydride (silicon dioxide), magnesium carbonate, calcium carbonate, aluminum hydroxide, aluminum oxide, aluminum silicate, magnesium silicate, magnesium aluminum silicate, silicon carbide, barium sulfate, calcium silicate, zeolite, calcined calcium sulfate (calcined calcium sulfate), etc. can be used. Inorganic pigments such as calcined gypsum), calcium phosphate, hydroxyapatite, boron nitride, etc.; inorganic microparticle powders such as titanium oxide, zinc oxide, cerium oxide, etc. with an average primary particle size of less than 100nm; bright powders such as bismuth oxychloride, mica titanium, iron oxide-coated mica, iron oxide-coated mica titanium, organic pigment-coated mica titanium, aluminum powder, etc.; magnesium stearate, zinc stearate, N-acyl lysine, polyurethane, polystyrene, nylon, polymethyl methacrylate, polymethyl silsesquioxane powder, organic polysiloxane Elastomer powder, cellulose other than the above cellulose powder, crystalline cellulose, polyethylene, cross-linked poly(methyl)acrylate, polyester, copolymer of styrene and acrylic acid, benzoguanamine, tetrafluoroethylene, cellulose acetate and other organic body pigments; Red No. 201, Red No. 202, Red No. 204, Red No. 205, Red No. 220, Red No. 226, Red No. 228, Red No. 405, Orange No. 203, Orange No. 204, Yellow No. 205, Yellow No. 4 Organic coloring pigments such as organic pigments such as Red No. 01 and Blue No. 404, lakes of water-soluble dyes (zirconium lake, barium lake, aluminum lake, etc.) such as Red No. 3, Red No. 104, Red No. 106, Red No. 227, Red No. 230, Red No. 401, Red No. 505, Orange No. 205, Yellow No. 4, Yellow No. 5, Yellow No. 202, Yellow No. 203, Green No. 3 and Blue No. 1, and natural pigments and their lakes; one or a combination of two or more thereof.
[0135] From the aspect of the feel in use and the persistence of makeup, the powder Y other than the cellulose powder is preferably subjected to a surface hydrophobization treatment. As the surface hydrophobization treatment, for example, a baking treatment using silicones such as methyl hydrogen polysiloxane and (dimethylpolysiloxane / methylpolysiloxane) copolymers, a fatty acid treatment such as stearic acid, a fatty acid metal soap treatment such as aluminum stearate or zinc stearate, an acylated amino acid treatment, a lipid amino acid treatment as a mixed treatment of an acylated amino acid (salt) and a fatty acid (salt), a fluorine treatment such as a perfluoroalkyl phosphate, a silylation treatment using trimethylsilane, an acid ester treatment such as isostearyl sebacate, and the like known surface hydrophobization treatments can be used.
[0136] In the solid powder cosmetics of the present embodiment, from the aspects of improving the sense of use such as the persistence of makeup and the adhesion and ductility on the skin, it is preferred to contain an inorganic body pigment treated with surface hydrophobization. As a preferred inorganic body pigment constituting the inorganic body pigment treated with surface hydrophobization, a plate-like powder with a volume average particle size of 1 μm to 50 μm can be cited. As a specific example of the plate-like powder, talc, sericite, mica, synthetic phlogopite, boron nitride, etc. can be cited. From the aspects of excellent formability, moist feeling and makeup persistence, the surface hydrophobization treatment in the inorganic body pigment treated with surface hydrophobization is preferably acid ester treatment, acylated amino acid treatment or lipid amino acid treatment. As a preferred specific example of surface hydrophobization treatment, isostearyl sebacate treatment as acid ester treatment, stearoyl glutamic acid Al treatment as acylated amino acid treatment, palmitoyl proline / palmitoyl glutamic acid Mg / palmitoyl sarcosine Na / palmitic acid Al composite treatment as lipid amino acid treatment, etc. can be cited.
[0137] Among the powders Y other than the above-mentioned cellulose powder, in particular, if spherical inorganic powders and organic powders are used, for example, spherical silica, polyurethane, polystyrene, nylon, polymethyl methacrylate, polymethylsilsesquioxane powder, organic polysiloxane elastomer powder, cellulose other than the above-mentioned cellulose powder, crystalline cellulose, cellulose acetate, etc., it is possible to effectively conceal pores, fine lines and other unevenness, thus becoming a preferred makeup look.
[0138] The content of the powder containing the cellulose powder (i.e., the total of the cellulose powder and the powder Y other than the cellulose powder) is preferably 60% to 99.9% by mass, more preferably 70% to 99% by mass, and particularly preferably 80% to 95% by mass relative to the total amount of the solid powder cosmetic. If the content of the powder containing the cellulose powder is less than 60% by mass, it is difficult to apply it to a makeup puff such as a sponge, and the resulting makeup film tends to be sticky.
[0139] In the case where the solid powder cosmetics of the present embodiment include a plate-like inorganic body pigment, the content of the plate-like inorganic body pigment is preferably 1% to 95% by mass, more preferably 5% to 90% by mass, and particularly preferably 10% to 85% by mass relative to the total amount of the solid powder cosmetics. Here, the plate-like shape is not particularly limited, for example, it refers to the particle shape of 5 or more by calculating each aspect ratio (length / thickness) after observing the particles using SEM (scanning electron microscope) and measuring each cross-sectional thickness and length, and the aspect ratio is calculated. In the case where the content of the plate-like inorganic body pigment is small, there is a tendency to lack adhesion (adhesion on the skin). On the other hand, if a large amount of plate-like inorganic body pigments are contained, it is possible to damage the moldability and drop strength. However, in the solid powder cosmetics of the present embodiment, even if the plate-like inorganic body pigment of more than 70% by mass is mixed, the cellulose powder also improves the moldability, so the moldability and drop strength are excellent.
[0140] When the solid powder cosmetic of the present embodiment includes spherical inorganic powder and / or organic powder, the content of the spherical inorganic powder and / or organic powder is preferably 1% to 40% by mass, more preferably 3% to 35% by mass, and particularly preferably 5% to 30% by mass relative to the total amount of the solid powder cosmetic. Here, spherical refers to a shape having a circularity of 0.8 to 1 obtained by the above-mentioned static image analysis method, for example. When the content is too small, the unevenness hiding effect is lacking, and when it is too large, the moldability is reduced.
[0141] (Moisturizer)
[0142] The solid powder cosmetics of this embodiment can be mixed with a moisturizer. As a moisturizer, for example, one or more of polyols, sugars, sugar alcohols, amino acids, peptides, water-soluble polymers, etc. can be used. In addition, as a moisturizer, for example, glycerol, diglycerol, propylene glycol, 1,3-butylene glycol, 1,2-pentanediol, dipropylene glycol, 1,3-propanediol, 1,2-hexanediol, heptanediol, 1,2-octanediol, ethylhexylglycerol, xylitol, sorbitol, maltitol, chondroitin sulfate, hyaluronic acid, collagen, sodium lactate, dl-pyrrolidonecarboxylate, roxburghii extract, yarrow extract, sweet osmanthus extract, etc. can be mixed.
[0143] (other)
[0144] The solid powder cosmetics of this embodiment may contain, in addition to the above-mentioned powders, oil components, and moisturizers, various ingredients commonly found in cosmetics, such as water-soluble ultraviolet absorbers, preservatives / antibacterial agents, fragrances, antioxidants, pH adjusters, chelating agents, cooling agents, anti-inflammatory agents, skin beautifying ingredients, vitamins, amino acids, nucleic acids, inclusion compounds, etc.
[0145] (Purpose, etc.)
[0146] The solid powder cosmetics of this embodiment are particularly excellent in making makeup cosmetics such as pressed powder (solid white powder), powder foundation, wet and dry dual-purpose foundation, water-only cake foundation, powder eye shadow, blush, facial toner, eyebrow pencil, etc.
[0147] Example
[0148] Next, the results of various tests performed are shown. The cellulose powder, silicone powder, and silica powder used in the test examples and reference examples were obtained as follows. It should be noted that "ELLEX (registered trademark)-S" manufactured by Daio Paper Co., Ltd. was used as the fine fibrous cellulose, and Fujifilm Wako Pure Chemical Industries, Ltd.'s special grade glycerin was used as the glycerin.
[0149] (Cellulose powder A)
[0150] The fine fibrous cellulose was mixed in an amount of 70% by mass and 30% by mass of glycerol based on the solid content to prepare a fine fibrous cellulose aqueous dispersion having a concentration of 3.0%. The aqueous dispersion was spray dried using a spray dryer (PRECI "P-260") to obtain cellulose powder A. The average particle size of cellulose powder A was 13.5 μm. The SEM image of cellulose powder A is shown in Figure 1 .
[0151] (Cellulose powder B)
[0152] The fine fibrous cellulose was mixed with water in an amount of 70% by mass and 30% by mass of glycerol based on solid content to prepare a fine fibrous cellulose aqueous dispersion. The aqueous dispersion was dried using a double drum dryer (Johnson Boiler's "John Millder JM-T model") at a drum rotation speed of 3 rpm and a drum surface temperature of 135°C to obtain a dried body, which was pulverized to obtain a cellulose powder B. The SEM image of the cellulose powder B is shown in FIG. Figure 2 .
[0153] (Cellulose powder C)
[0154] As cellulose powder C, "Wako first-grade cellulose, powder, through 38 μm (400 mesh)" produced by Fujifilm Wako Pure Chemical Industries, Ltd. was used. It should be noted that the cellulose raw material of cellulose powder C is not the fine fibrous cellulose used in the present invention. The SEM image of cellulose powder C is shown in FIG. Figure 3 .
[0155] (Cellulose powder D)
[0156] Cellulose powder D was made from "CELLULOBEADS" produced by Daito Chemical Industry Co., Ltd. It should be noted that the cellulose raw material of cellulose powder D was not the fine fibrous cellulose used in the present invention. The SEM image of cellulose powder D is shown in FIG. Figure 4 .
[0157] (Cellulose powder E)
[0158] The fine fibrous cellulose was dispersed in water at a concentration of 3.0% based on solid content to prepare a fine fibrous cellulose aqueous dispersion. No additives were added. The aqueous dispersion was spray-dried using a spray dryer (PRECI "P-260") to obtain cellulose powder E.
[0159] (Silicone powder)
[0160] As the silicone powder, "KSP-100" manufactured by Shin-Etsu Chemical Co., Ltd. was used. The SEM image of the silicone powder is shown in FIG. Figure 5 .
[0161] (Silicon dioxide powder)
[0162] As the silica powder, "CHIFFONSIL P-3R" produced by JGC Catalysts & Chemicals Co., Ltd. was used. The SEM image of the silica powder is shown in FIG. Figure 6 .
[0163] The physical properties of the obtained powder were measured. The measurement items of the physical properties are as shown in Table 1. The measurement items of the physical properties were measured according to the following procedures.
[0164] The bulk specific gravity is measured by a static method in accordance with JIS-K-5101-12-1 (2004).
[0165] Regarding the moisture content, 5 g of the powder was allowed to stand for 24 hours by a heat drying method, and the weight before and after drying was calculated. More specifically, a powder that was allowed to stand for more than 24 hours under a humidity of 50% (i.e., the powder before drying) was dried at a temperature of 105° C. for 24 hours to obtain a powder after drying, and the moisture content was calculated from the weight of the powder before drying and the weight of the powder after drying by the following mathematical formula [Figure 1].
[0166] [Number 1]
[0167] (Water content (%)) = [((weight of powder before drying) - (weight of powder after drying)) / (weight of powder after drying)] × 100
[0168] The compressive strength was measured with reference to JIS R1639-5 "Fine ceramics - Determination of particle properties - Part 5: Single particle compressive strength" using Microautograph "MST-I", a micro-part strength evaluation device produced by Shimadzu Corporation.
[0169] The specific surface area (BET multipoint method) was measured using the Shimadzu TriStar II 3020N surface area measuring instrument. 2 Gas" for measurement.
[0170] The cumulative distribution of equivalent circle diameters (number basis, cumulative 50% diameter), the cumulative distribution of equivalent circle diameters (volume basis, cumulative 50% diameter), the aspect ratio, and the circularity were measured using "Morphologi 4" manufactured by Spectris Corporation.
[0171] The mode diameter, median particle size (cumulative 50% diameter), average particle size, cumulative 10% diameter, and cumulative 90% diameter were measured by a dry method without scattering the water attached to the cellulose powder using a measuring device in accordance with ISO-13320 (2009), specifically, using a laser diffraction / scattering particle size distribution measuring device (particle size distribution) "LA-960V2".
[0172] In addition, the pulp viscosity of cellulose and the average degree of polymerization of cellulose were measured for each of the obtained cellulose powders A to D. The pulp viscosity is a value measured in accordance with TAPPI T 230. The average degree of polymerization of cellulose refers to the viscosity average degree of polymerization measured in accordance with JIS-K6726.
[0173] [Table 1]
[0174]
[0175] (Test example and reference example)
[0176] The powders obtained as described above were mixed in the mixing ratios shown in Tables 2 and 3. Specifically, for Test Examples 1 and 2 and Reference Examples 1 to 3 in Table 2, a mixture of any one of the powders of Components No. 1 to 5 and Components No. 6 to 13 was mixed at 10,000 rpm (scale 50) for 10 seconds using a sample mill ("SK-M10" produced by Kyoritsu Riko Co., Ltd.) to prepare a mixture as an intermediate product. Next, a substance obtained by uniformly mixing the components No. 14 to 19 in advance was mixed with the above mixture, and further mixed for 30 seconds using the above sample mill to obtain powder compositions for Test Examples 1 and 2 and Reference Examples 1 to 3, respectively.
[0177] For Test Example 3 and Reference Examples 4 to 7 in Table 3, a mixture of any one of the powders of Components No. 1 to 4 and Components No. 5 to 13 was mixed at 10,000 rpm (scale 50) for 10 seconds using a sample mill (product "SK-M10" of Kyoritsu Riko Co., Ltd.) to prepare a mixture as an intermediate product. Next, a mixture prepared by uniformly mixing Components No. 14 to 19 (for Reference Example 7, Components No. 14 to 20) in advance was mixed with the above mixture, and further mixed for 30 seconds using the above sample mill to obtain powder compositions for Test Example 3 and Reference Examples 4 to 7, respectively.
[0178] [Table 2]
[0179]
[0180] ※1Product name: CELLULOBE ADS D-10 manufactured by Daito Kasei Kogyo Co., Ltd. ※2Product name: KSP-100 manufactured by Shin-Etsu Chemical Kogyo Co., Ltd.
[0181] ※3 Product name: CHIFFONSIL P-3R manufactured by JGC Catalysts & Chemicals Co., Ltd.
[0182] ※4Product name: NAI-TALC JA-46R manufactured by Miyoshi Chemicals Co., Ltd.
[0183] ※5 Product name: HS-TALC JA-46R manufactured by Miyoshi Chemicals Co., Ltd.
[0184] ※6 Product name: KSG-16 manufactured by Shin-Etsu Chemical Co., Ltd.
[0185] [Table 3]
[0186]
[0187] ※1Product name: CELLULOBE ADS D-10 manufactured by Daito Chemical Industry Co., Ltd.
[0188] ※2 Cellulose powder E is made by spray drying only the fine fibrous cellulose without any additives.
[0189] The average particle size is 15 μm.
[0190] ※3 Product name: NAI-TALC JA-46R manufactured by Miyoshi Chemicals Co., Ltd.
[0191] ※4Product name: SA-TALC JA-46R manufactured by Miyoshi Chemicals Co., Ltd.
[0192] ※5 Product name: HS-TALC JA-46R manufactured by Miyoshi Chemicals Co., Ltd.
[0193] ※6 Product name: KSG-16 manufactured by Shin-Etsu Chemical Co., Ltd.
[0194] The powder composition obtained by the above operation steps was filled into an aluminum metal disk with a diameter of 54 mmφ, and a press machine (Sanshin Seiki Co., Ltd. semi-automatic press "SSPP (hydraulic cylinder diameter 80 mmφ)") was used to press and mold at the pressing pressure shown in Table 4 to obtain Test Examples 1 to 3 and Reference Examples 1 to 7. The hardness of the obtained Test Examples 1 to 3 and Reference Examples 1 to 7 was measured. The hardness was measured using the "Olsen Hardness Tester" produced by Ueshima Manufacturing Co., Ltd., which is a constant load indentation hardness tester, under the condition of a load of 1 pound (= 453.59 g). The results of the hardness measurement are shown in Table 4.
[0195] [Table 4]
[0196]
[0197] (Performance evaluation test)
[0198] The test examples and reference examples were subjected to a performance evaluation test. The test items of the performance evaluation test were drop strength, ease of taking on a puff, smoothness when applied on the skin, moist feeling when applied on the skin, and adhesion to the skin. The results of the performance evaluation test are shown in Table 5.
[0199] [Table 5]
[0200]
[0201] The drop strength test is carried out according to the following operating steps.
[0202] (1) From a height of 30 cm above the plane of a horizontally placed concrete block, the test example or reference example was freely dropped with the plane portion of the test example or reference example horizontal so as to collide with the plane of the concrete block.
[0203] (2) Repeat the above-mentioned operation (1) until the test example or reference example breaks.
[0204] (3) The case where the number of trials of the above (1) (2) until the test example or reference example broke was 11 times or more was evaluated as judgment A, the case where it was 8 times or more and 10 times or less was evaluated as judgment B, the case where it was 5 times or more and 7 times or less was evaluated as judgment C, and the case where it was 4 times or less was evaluated as judgment D. Regarding the description of the drop strength in Table 5, for example, when the test example or reference example broke after 10 trials, it is described as "B (10)" or the like.
[0205] Each test of the ease of taking on the puff, the smoothness when applied on the skin, the moist feeling when applied on the skin, and the adhesion to the skin was conducted as follows. Ten female professional judges were asked to evaluate the test examples and reference examples.
[0206] Specifically, the ease of taking the powder on the puff, the smoothness when applied to the skin, the moist feeling when applied to the skin, and the adhesion to the skin were evaluated according to the following three levels: a good feeling was scored as 2, a feeling that was difficult to judge was scored as 1, and a poor feeling was scored as 0. The average score was calculated from the obtained scores, and if the average score was 1.5 or more, it was evaluated as judgment A, if it was 1.2 or more and less than 1.5, it was evaluated as judgment B, if it was 0.5 or more and less than 1.2, it was evaluated as judgment C, and if it was less than 0.5, it was evaluated as judgment D.
[0207] The following can be seen from the results of Table 5. When comparing Test Examples 1 and 2 and Reference Examples 1 to 3, which have the same powder amount (90% by mass) and the total amount of oil and moisturizer (10% by mass), Test Example 1 containing cellulose powder A is excellent in all items, while Reference Example 1 containing commercially available spherical cellulose and Reference Example 3 containing commercially available spherical silica are significantly inferior in terms of ease of taking on a puff, moist feeling when applied, and adhesion to the skin. Reference Example 2 containing a silicone elastomer as an elastic powder has the same cosmetic performance as Test Example 1, such as moist feeling, but is much inferior to Test Example 1 in drop strength. Test Example 2 containing cellulose powder B having a large average particle size is excellent in drop strength, but is slightly inferior to Test Example 1 in terms of ease of taking on a puff, smoothness when applied, moist feeling when applied, and adhesion to the skin.
[0208] Comparing Test Example 3 and Reference Examples 4 to 7, which have the same powder amount (95.95% by mass) and the total amount of oil and moisturizer (4.05% by mass), Test Example 3 is excellent in all items even when the total amount of oil and moisturizer is small, while Reference Examples 4 to 6 are insufficient in drop strength. On the other hand, Reference Example 4 containing commercially available cellulose powder C has poor drop strength and slightly poor moist feeling. In addition, Reference Example 6 containing cellulose particles E produced from fine fibrous cellulose without additives has poor drop strength and slightly poor smoothness, moist feeling, etc.
[0209] In Reference Example 7, cellulose powder E, which is composed of aggregates containing fine fibrous cellulose and does not contain any additive, was used. Although the drop strength was improved, the smoothness and adhesion to the skin were poor. It should be noted that the glycerin contained in Reference Example 7 was added as a component of the moisturizing agent in the mixture as the above-mentioned intermediate product, and did not constitute an aggregate.
[0210] Industrial Applicability
[0211] The present invention can be used as makeup base, loose powder, foundation, base makeup and other cosmetics.
Claims
1. A solid powder cosmetic, characterized in that: It contains cellulose powder with an average particle size of 1 μm to 25 μm and an aspect ratio of 0.6 to 0.
9. The cellulose powder is an aggregate containing an additive and fine fibrous cellulose having an average fiber width of 1 nm to 500 nm.
2. The solid powder cosmetic according to claim 1, wherein: The cellulose powder is formed by agglomeration of the fine fibrous cellulose.
3. The solid powder cosmetic according to claim 1, comprising 60% to 99.9% by mass of the powder comprising the cellulose powder and 0.1% to 40% by mass of oil.
4. The solid powder cosmetic according to claim 1, wherein: The additive is glycerol.
5. The solid powder cosmetic according to claim 1, wherein: The moisture content of the cellulose powder in an atmosphere with a humidity of 50% is 1% to 15%.
6. The solid powder cosmetic according to claim 1, wherein: The bulk density of the cellulose powder is 0.5 g / cm 3 the following.
7. The solid powder cosmetic according to claim 1, wherein: The specific surface area of the cellulose powder is 1.0 m 2 / g or above.
8. The solid powder cosmetic according to claim 1, comprising 1% to 99% by mass of the cellulose powder.
9. The solid powder cosmetic according to claim 1, wherein: The cellulose pulp viscosity of the cellulose powder is 1.0 mPa·s to 7.0 mPa·s.
10. The solid powder cosmetic according to claim 1, which is a base makeup cosmetic.
Citation Information
Patent Citations
Solid powdery cosmetic containing organic powder
JP2002080325A
Powder cosmetic
JP2021098674A
Makeup cosmetic
WO2018194050A1